2009
DOI: 10.1128/iai.00546-09
|View full text |Cite
|
Sign up to set email alerts
|

Leptospira interrogans Binds to Human Cell Surface Receptors Including Proteoglycans

Abstract: Leptospirosis is a global public health problem, primarily in the tropical developing world. The pathogenic mechanisms of the causative agents, several members of the genus Leptospira, have been underinvestigated. The exception to this trend has been the demonstration of the binding of pathogenic leptospires to the extracellular matrix (ECM) and its components. In this work, interactions of Leptospira interrogans bacteria with mammalian cells, rather than the ECM, were examined. The bacteria bound more efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
61
0
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(79 citation statements)
references
References 40 publications
9
61
0
8
Order By: Relevance
“…Pathogenic Leptospira strains have been shown to bind the soluble complement-regulatory proteins FH, FHL-1, FHR-1, and C4BP (4-7) and several ECM and plasma molecules, including laminin, collagens, fibronectin, elastin, tropoelastin, proteoglycans, fibrinogen, and plasminogen (20,21,27,28). Here we demonstrate that this spirochete also interacts with human vitronectin.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Pathogenic Leptospira strains have been shown to bind the soluble complement-regulatory proteins FH, FHL-1, FHR-1, and C4BP (4-7) and several ECM and plasma molecules, including laminin, collagens, fibronectin, elastin, tropoelastin, proteoglycans, fibrinogen, and plasminogen (20,21,27,28). Here we demonstrate that this spirochete also interacts with human vitronectin.…”
Section: Discussionmentioning
confidence: 80%
“…Immunohistochemical studies allowed detection of vitronectin in a variety of normal human tissues, including the liver, lungs, kidneys, and blood vessel walls (15,18). Previous reports have demonstrated that leptospires bind several extracellular matrix components (20,21), but interaction of these particular spirochetes with vitronectin has never been evaluated.…”
mentioning
confidence: 99%
“…Accordingly, leptospires employ surface-exposed proteins to bind to a wide range of host ligands, including laminin, collagen, cellular and plasma fibronectin, elastin, proteoglycans, fibrinogen, and plasminogen (13,30,31,36,37). LipL32 binds to plasma fibronectin, collagen types I, IV, and V, laminin, and plasminogen (11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…Treponema denticola também expressa uma proteína que interage com FH (FhbB) e assim escapa da morte pela ativação da via alternativa do complemento (Miller et al, 2012). As leptospiras patogênicas interagem com diversos componentes de matriz extracelular como laminina, colágeno tipo I e IV, fibronectina, elastina e proteoglicanos (Breiner et al, 2009;Ito, Yanagawa,1987;. Cabe ressaltar que leptospiras patogênicas são micro-organismos altamente invasivos, capazes de aderir e invadir células hospedeiras mais eficientemente do que as estirpes não patogênicas e saprófitas (Fraga et al, 2011;Liu, 2007).…”
Section: Noguchi São Capazes De Interagir Tambémunclassified